Strategies to achieve adequate vitamin A intake for young children: options for Cameroon. Issue 1 (3rd December 2019) - Vosti, Stephen A.; Kagin, Justin; Engle‐Stone, Reina; Luo, Hanqi; Tarini, Ann; Clermont, Adrienne; Assiene, Jules Guintang; Nankap, Martin; Brown, Kenneth H.
Abstract: Meeting children's vitamin A (VA) needs remains a policy priority. Doing so efficiently is a fiscal imperative and protecting at‐risk children during policy transitions is a moral imperative. Using the Micronutrient Intervention Modeling tool and data for Cameroon, we predict the impacts and costs of alternative VA intervention programs, identify the least‐cost strategy for meeting targets nationally, and compare it to a business‐as‐usual (BAU) strategy over 10 years. BAU programs effectively cover ∼12.8 million (m) child‐years (CY) and cost ∼30.1 m; ∼US2.34 per CY effectively covered. Improving the VA‐fortified oil program, implementing a VA‐fortified bouillon cube program, and periodic VA supplements (VAS) in the North macroregion for 3 years effectively cover ∼13.1 m CY at a cost of ∼US9.5 m, or ∼US0.71 per CY effectively covered. The tool then identifies a sequence of subnational policy choices leading from the BAU toward the more efficient strategy, while addressing VA‐attributable mortality concerns. By year 4, fortification programs are predicted to eliminate inadequate VA intake in the South and Cities macroregions, but not the North, where VAS should continue until additional delivery platforms are implemented. This modeling approach offers a concrete example of the strategic use of data to follow the Global Alliance for VA framework and do so efficiently. Abstract : The objectives of this paper are to apply the Micronutrient Intervention Modeling tool to: update the model with a revised set of vitamin A (VA) intervention programs and data to support them, and identify concrete subnational policy pathways (sequences of VA program modifications) in Cameroon, which are guided by the Global Alliance for Vitamin A framework.